Virus Protein and Nucleoprotein Complexes (Subcellular Biochemistry,, 2018)
The Subcellular Biochemistry series has recently embarked upon an almost encyclopaedic coverage of topics relating to the structure and function of macromolecular complexes (Volumes 82, 83 and 87). The present multi-author text covers numerous aspects of current research into molecular virology, with emphasis upon viral protein and nucleoprotein structure and function. Structural data from cryo-electron microscopy and X-ray crystallography is displayed throughout the book. The 17 chapters in the book cover diverse interesting topics, all currently under investigation, contributed by authors who are active actively involved in present-day research. Whilst structural aspects predominate, there is much consideration of the structure-function relationship. In addition, the book correlates with and extends from Volume 68 of the series "Structure and Physics of Viruses: An Integrated Textbook". This book is directed primarily at professionals that work in the broad field of Structural Biology and will be of particular interest to Structural Virologists. The editors, David Bhella and Robin Harris, have much experience in virology and protein structure, respectively. Dr Bhella is Director of the Scottish Macromolecular Imaging Centre. Professor Robin Harris is the long-standing Series Editor of the Subcellular Biochemistry series. He has edited and contributed to several books in the series.